2015
DOI: 10.1007/s00586-015-3779-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the laminoplasty opening size and the laminoplasty opening angle, increased sagittal canal diameter and the prediction of spinal canal expansion following open-door cervical laminoplasty

Abstract: Objective To clarify the relationship between the laminoplasty opening size (LOS), the laminoplasty opening angle (LOA) and the increase in sagittal canal diameter (SCD) and to predict the amount of canal enlargement during open-door cervical laminoplasty (ODCL). Methods Formula describing the relationship between LOS and LOA, the increase in SCD was deduced. The parameters of pre-and postoperative computed tomography scans of 36 patients who had undergone laminoplasty surgery were measured by picture archivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…It was found in other studies that recovery of post-operative nerve function was closely related to the SCD and LOS [15,21]. The post-operative SCD increment seems to be more important than spinal canal area enlargement in alleviating spinal cord compression [10,22].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It was found in other studies that recovery of post-operative nerve function was closely related to the SCD and LOS [15,21]. The post-operative SCD increment seems to be more important than spinal canal area enlargement in alleviating spinal cord compression [10,22].…”
Section: Discussionmentioning
confidence: 96%
“…Itoh and Tsuji reported that a SCD increment of 4.1 mm is optimum and could be obtained via LOS enlargement to 8 mm [14]. Some researchers proposed the optimal post-operative SCD increment to be 4–5 mm in SDCL [1,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 6 8 ] Some studies noted that the lamina open angle should be small, excessive opening angle did not reduce the incidence of reclosure but increase occurrence of complications. [ 9 13 ] However, they did not continue to explore the relationship between the opening angle and axial symptoms. The objective of the present study was to explore the effect of different laminae open angles on postoperative axial symptoms and to discuss the possible mechanism of the impact of different open angles on axial symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ODL has been frequently opted by surgeons because from the long-term follow-up study, it has offered greater patient satisfaction with improvement on the motor scale, less risk than radical anterior approach, and superiority over conventional laminectomy. This procedure can preserve cervical spine stability, prevent canal stenosis due to scar formation, and cause less frequent axial pain [ 6 - 8 ].…”
Section: Introductionmentioning
confidence: 99%